Bilateral intracranial EEG with corpus callosotomy may uncover seizure focus in nonlocalizing focal epilepsy. (January 2015) - Chen, Po Ching; Baumgartner, James; Seo, Joo Hee; Korostenskaja, Milena; Lee, Ki Hyeong
Highlights: Complete corpus callosotomy lateralized seizures in 7 of 9 non-localizing patients. Complete CC localized seizures in 4 of 9 patients leading to respective surgery. Bilateral iEEG combined with complete CC can be safely performed. The multi-stage surgical procedure using iEEG with CC is a viable option for catastrophic non-lateralizing epilepsy. Abstract: Purpose: To evaluate the value of a new multi-stage surgical procedure using bilateral intracranial electroencephalogram (iEEG) prior and post complete corpus callosotomy (CC) for epileptogenic focus localization. Method: Thirty patients with drug-resistant epilepsy underwent bilateral iEEG monitoring to localize epileptogenic focus for surgical treatment. Among them, bisynchronous epileptogenic activities were found in 9 pediatric patients. These 9 patients then received complete CC and continued bilateral iEEG monitoring for further seizure localization. Final surgical treatment decisions were made based on the bilateral iEEG findings post complete CC. The entire multi-stage procedure was performed during the same hospital stay. We retrospectively studied the data from the 9 patients. Results: Seizure onset was lateralized in 3 patients who later received functional hemispherectomy. In another 4 patients, seizure onset was localized, resulting in resective surgery. Bilateral multiple subpial transection was performed on 1 patient with identified bilateral independent seizure onset. One patient did not have seizures following complete CC leading to removal of electrodes without any further resection. Subsequent follow-up showed favorable outcome in all patients: seizure-free in 7, more than 90% reduction in 2. None of the patients experienced surgery related complications during the procedure and follow-up period. Conclusion: The multi-stage surgical procedure utilizing iEEG monitoring with CC is a viable option for select patients with catastrophic non-localizing epilepsy. Further study is necessary to find the optimal selection criteria for use of this novel approach.